Baluara Port in Maritime Historical Perspective - Hisna (Indonesian Journal of Multidisciplinary Scientific Studies, 2025)
This article examines Baluara Port, located in Baluara Village, Batukara Subdistrict, Muna Regency. The port functions as a docking and operational site for wooden motor vessels and speedboats, facilitating passenger transport and the loading and unloading of goods along the Baluara–Raha and Raha–Baluara routes. This study employs a maritime historical approach, applying the historical method as formulated by Gottschalk (1975: 18–32), which consists of heuristics, source criticism, interpretation, and historiography. In addition, field observations and interviews were conducted at the research site to complement documentary sources. The findings indicate that Baluara Port was officially inaugurated in 1996. Since then, wooden motor vessels have operated regularly, transporting both passengers and agricultural produce. These vessels have a passenger capacity of approximately 35–40 persons and can carry cargo loads of 2–3 tons, primarily consisting of bananas, coconuts, copra, and other agricultural products cultivated by the local community. In the early 2000s, speedboats were introduced at Baluara Port. These vessels serve functions similar to wooden motor vessels, accommodating commercial goods, 20–25 passengers, and motorcycles. Both speedboats and wooden motor vessels operate on the Baluara–Raha and Raha–Baluara routes, with an average travel time of approximately one hour. From a social perspective, Baluara Port serves as a meeting point and a space of interaction for communities traveling between Baluara and Raha. Economically, the port facilitates and streamlines the transportation of agricultural commodities from Baluara and its surrounding areas to Raha. Thus, both socially and economically, Baluara Port plays a significant role in supporting the livelihood and mobility of the Baluara community and its neighboring regions.